AoMYB114 transcription factor regulates anthocyanin biosynthesis in the epidermis of tender asparagus stems - Li, Yanwen; Li, Mengyao; Guo, Zheng; Liu, Junting; Chen, Peiran; Lu, Wei; Jiang, Chengyao; Xiao, Jiachang; Lei, Fengyun; Zheng, Yangxia (Frontiers in Plant Science, 2025)
IntroductionAsparagus is a valuable vegetable, and its edible part is a tender stem. The color of the tender stem epidermis is an important trait. In particular, purple asparagus is rich in anthocyanins. However, the molecular mechanisms underlying anthocyanin accumulation in purple asparagus remains unclear.MethodsThe white variety ‘Jinguan’ (JG), the green variety ‘Fengdao 2’ (FD), and the purple variety ‘Jingzilu 2’ (JZ) were compared using physiological and transcriptomic analysis. High-performance liquid chromatography and real-time quantitative polymerase chain reaction were employed to detect anthocyanins and validate gene expression.ResultsCyanidin 3-glucoside and cyanidin 3-rutinoside were detected as the main anthocyanins in JZ. Transcriptome data demonstrated that 4,694 and 9,427 differentially expressed genes (DEGs) were detected in the JZ versus FD and JZ versus JG control groups, respectively. These DEGs were significantly enriched in pathways associated with anthocyanin accumulation, including phenylalanine metabolism, phenylpropanoid biosynthesis, and flavonoid biosynthesis. A total of 29 structural genes related to anthocyanin biosynthesis were identified. The expression of these structural genes was higher in JZ than in FD and JG, thereby activating the anthocyanin biosynthesis pathway. Additionally, a candidate gene, AoMYB114, was identified based on transcriptomic data. The expression of AoMYB114 was associated with anthocyanin accumulation in different tissues. Further research found that overexpression of AoMYB114 activated the anthocyanin biosynthesis pathway. It promoted leaf pigment accumulation in transgenic Arabidopsis.DiscussionThese findings demonstrate that AoMYB114 positively regulated anthocyanin biosynthesis. This study elucidates the molecular mechanism underlying purple coloration in asparagus. It provides important insights for improving asparagus quality and for breeding high-anthocyanin varieties.